2022
DOI: 10.1182/blood.2022016901
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease–driven treatment intensification with sequential addition of ibrutinib to venetoclax in R/R CLL

Abstract: Undetectable MRD (uMRD) is achievable in patients with CLL with the BCL2-inhibitor venetoclax alone or combined with the BTK-inhibitor ibrutinib. This phase 2 multicenter MRD-driven study was designed to discontinue treatment upon reaching uMRD4(<10-4) in patients with relapsed/refractory CLL receiving venetoclax monotherapy or after the addition of ibrutinib. Primary endpoint of the study was proportion of uMRD4 with venetoclax+/-ibrutinib. Secondary endpoints were ORR, PR, CR, PFS, DOR, OS, and safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Consistent with our observations, a handful of studies with a small number of cases and a cohort study of 74 patients by Mato et al concluded that the efficacy of BTKi therapy does not seem to be altered by prior venetoclax treatment [ 11 , 37 , 38 , 39 ]. Although sequential resistance to both BCL2 and BTK inhibition associated with dismal outcomes and poor prognosis may occur in some patients, venetoclax plus ibrutinib combination therapy or venetoclax retreatment seem to be promising approaches to address double-class-resistant cases, provided that dual-resistant subclones are absent in the selected patients [ 21 , 29 , 33 , 40 , 41 , 42 ]. Considering the updated data from the phase 2 CLARITY trial, chemotherapy-free, time-limited venetoclax plus ibrutinib therapy targeting distinct CLL subpopulations can provide synergistic activity in R/R CLL patients, overcoming acquired resistance and conferring complete response rates comparable with other venetoclax-based regimens [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observations, a handful of studies with a small number of cases and a cohort study of 74 patients by Mato et al concluded that the efficacy of BTKi therapy does not seem to be altered by prior venetoclax treatment [ 11 , 37 , 38 , 39 ]. Although sequential resistance to both BCL2 and BTK inhibition associated with dismal outcomes and poor prognosis may occur in some patients, venetoclax plus ibrutinib combination therapy or venetoclax retreatment seem to be promising approaches to address double-class-resistant cases, provided that dual-resistant subclones are absent in the selected patients [ 21 , 29 , 33 , 40 , 41 , 42 ]. Considering the updated data from the phase 2 CLARITY trial, chemotherapy-free, time-limited venetoclax plus ibrutinib therapy targeting distinct CLL subpopulations can provide synergistic activity in R/R CLL patients, overcoming acquired resistance and conferring complete response rates comparable with other venetoclax-based regimens [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained were superimposable with 60% of patients achieving uMRD in bone marrow and 4.5-year PFS and OS of 70% and 97%, respectively [36,37]. In patients with del(17p) and/or mutated TP53 (27/159, 17% of patients), ORR and CR were superimposable compared to the treated population (96% vs. 96%, and 56% vs. 55%, respectively); slightly lower was the estimated 24-month PFS, which was 96% (95% CI, [91][92][93][94][95][96][97][98] in patients without del(17p), and 84% (95% CI, 63-94) in patients with del(17p)/mutated TP53. In the same study, 154 patients underwent secondary randomization after 15 cycles according to MRD status (MRD cohort), and at the end of the 15-cycle treatment 68% of patients achieved uMRD [38].…”
Section: Ibrutinib-venetoclaxmentioning
confidence: 97%
“…Retreatment with the same class should be considered in the case of discontinuation for reasons other than progression, in accordance with what is discussed in the previous sections. In the case of relapse after fixed-duration therapy with both (venetoclax + cBTKi) in patients who achieve a response and relapse after a discrete period of time, restarts of either venetoclax [96] or ibrutinib [37] are currently under investigation in clinical trials, with promising results. In the CAPTIVATE trial, to date, 22 patients with progressive disease after completion of Ibr + Ven at fixed duration have been retreated with ibrutinib.…”
Section: Previous Btki and Venetoclax (Double-exposed And Double-refr...mentioning
confidence: 99%
“…Over half of the patients in this study had TP53 aberration (28 of 45 patients) and the rate of BM uMRD after 12 cycles of I + V was 57%. Another study by Scarfo et al [70] tested the addition of ibrutinib to venetoclax in RR CLL patients who had detectable MRD after 12 cycles of initial treatment with venetoclax (V + I). Despite all patients in this study being previously treated with CIT and a third of the study population having TP53 aberration (11 of 38 patients), 84% achieved uMRD in both PB and BM after a median of 7 months of V + I.…”
Section: Tp53 Aberrationmentioning
confidence: 99%